Development and factor structure of the perceptions of concussion inventory for athletes (PCI-A). (23rd February 2021) - Schmitt, Ara J.; Beidler, Erica; O'Connor, Siobhan; Eagle, Shawn; Wallace, Jessica; Anderson, Morgan; Kontos, Anthony
ABSTRACT: Purpose : This study evaluated the factor structure of the Perceptions of Concussion Inventory for Athletes (PCI-A) using exploratory factor analytic (EFA) techniques in a sample of collegiate student-athletes. Perception differences by sex and sport-related concussion (SRC) risk level were explored. Methods : This cross-sectional-design study included 298 male and 183 female collegiate student-athletes from 18 sports at six institutions. Participants completed a demographic and concussion history survey, and the PCI-A. Results : The EFA revealed a 6-factor solution (Anxiety, Effects, Clarity, Treatment, Control, and Symptom Variability) that accounted for 56.1% of the variance in responses. Female collegiate student-athletes displayed statistically higher levels of Anxiety, Clarity, Symptom Variability, and Control than males. Lower concussion risk sport athletes reported statistically higher levels of anxiety surrounding SRC and concerns relating to the long-term and major effects of an SRC. Conclusions : This study provides evidence that the PCI-A is an acceptable measure to examine the perceptions of collegiate student-athletes regarding SRC. The findings supported a six-factor structure of the PCI-A in the current study for collegiate student-athletes compared to the seven-factor structure indicated in previous research. The findings reveal sex and concussion risk sport differences in PCI-A responses.